The material culture of basketry : practice, skill and embodied knowledge - Bunn, Stephanie; Mitchell, Victoria (London : Bloomsbury Publishing, 2023)
Part 1. Materials and Processes: from plant to basket and beyond -- Part 2. Basketry as Maths, Pattern and Engineering: growth, form and structure -- Part 3. Gathering Knowledge: basketry as a medium of memory, belonging and evocation -- Part 4. Basketry: memory, healing, and recovery.